Faktor-Faktor Yang Mempengaruhi Struktur Modal Perusahaan Manufaktur Di BEI Periode 2015-2017 - Viviana, Lukman Surjadi, (Jurnal Ekonomi, 2019)
Thisistudy aims to examine the effect of company size, profitability, and business risk on capital structure in listed manufacturing companies in Indonesian Stock Exchange period 2015-2017. This study use 24 manufacturing companies as sample in this study and also use multipleiregression analysis.iThe results of this study indicate that company size has a significant positive effectnon capitalustructure while profitability and business risk has a not significant negative effect on capital structure.